Photocatalytic self-cleaning silicate type lithium ion sieve and preparation method thereof

By using bismuth terbium co-doped spodumene material in lithium ion sieve, a photocatalytic self-cleaning core-shell structure is formed, which solves the reduction in selective adsorption performance of lithium ion sieve and poor anti-pollution ability in complex dilute lithium aqueous solutions. The problem is that efficient and stable lithium ion adsorption and extraction effects are achieved.

CN119430208APending Publication Date: 2025-02-14TIANJIN VOCATIONAL INST
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411572112.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing lithium-ion sieves have decreased selective adsorption performance in complex dilute lithium aqueous solutions, and have problems with high solubility and poor anti-pollution ability, making it difficult to effectively extract and enrich dilute lithium.

Method used

Spodumene co-doped with bismuth terbium is used as the material for photocatalytic self-cleaning silicate-type lithium-ion sieve, and is synthesized and coated on a natural spodumene support by sol-gel method to form a core-shell structure and improve lithium ions. The adsorption desorption speed and saturated adsorption capacity are enhanced by high-temperature transformation and acidification deliquification treatment.

Benefits of technology

The high lithium ion saturated adsorption capacity of lithium ion sieve (18-27mg/g) was achieved, and the lithium ion saturated adsorption capacity decreased by only 3%-5% after 5 adsorption and desorption cycles, which significantly improved the anti-pollution ability and use. life.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a photocatalytic self-cleaning silicate type lithium ion sieve and a preparation method thereof, the surface of a natural spodumene carrier is coated with a bismuth terbium photocatalytic material co-doped spodumene component mixed hydrosol, and the pH value of the mixture hydrosol is adjusted to 4-6 to form gel; further carrying out compression molding, drying, high-temperature transformation and acidification lithium removal on the gel to form the photocatalytic self-cleaning silicate type lithium ion sieve. The chemical composition of the material is HAl (1-x-y) BixTbySi2O6 / nH (1-z) LizAlSi2O6, x is equal to 0.02 to 0.2, y is equal to 0.01 to 0.1, z is equal to 0.50 to 0.90, and n is equal to 1 to 3; when the adsorbent is used for adsorbing lithium ions in simulated oilfield water, the saturated adsorption capacity of the lithium ions is 18-27mg / g, and the saturated adsorption capacity of the lithium ions is only reduced by 3%-5% after five times of adsorption and desorption cycles; the material can be used for adsorbing and extracting lithium from salt lake brine, seawater, oil and gas field water and industrial wastewater. Bismuth and terbium are co-doped, so that the lithium ion sieve is endowed with a photocatalytic self-cleaning function and anti-pollution capacity, and the lithium ion saturation adsorption capacity of the lithium ion sieve is improved; the bismuth-terbium co-doping thermal chemical reaction and the high-temperature transformation treatment are completed in one step, and the preparation process is energy-saving and environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a photocatalytic self-cleaning silicate type lithium ion sieve and a preparation method thereof, and belongs to the field of new energy materials. Background Art

[0002] Lithium is mainly stored in spodumene ore, seawater, salt lake brine, oil and gas field water and lithium-containing industrial wastewater. Due to the limited reserves of spodumene ore, the long-term goal of developing lithium resources is to use lithium ion sieves to selectively enrich and extract lithium from dilute lithium aqueous solutions. The key to extracting lithium from dilute lithium aqueous solutions is to design and prepare high-performance lithium ion sieves.

[0003] The existing lithium-manganese, titanium and aluminate ion sieve products have greatly reduced selective adsorption performance in pilot or industrial experiments. On the one hand, the chemical composition of the actual dilute lithium aqueous solution is very complex and causes interference; on the other hand, the natural dilute lithium aqueous solution has been contaminated by organic matter, and the pollutants have reduced the performance of the lithium ion sieve. The industry is in urgent need of lithium ion sieves with anti-pollution or self-cleaning functions.

[0004] Patent CN06390951A discloses a lithium ion sieve adsorbent with self-cleaning function, its preparation method and use. Titanium oxide is coated on the surface of manganese-based lithium ion sieve to prepare a lithium ion sieve with self-cleaning function. The super-hydrophilic property of titanium oxide is used to flush impurities or organic matter adhering to the surface of the adsorbent, thereby improving the stability of the adsorbent and extending its service life. However, its actual dissolution rate in acidic desorption liquid is as high as 20%-30%. In the past 20 years, although the development boom of two rounds of lithium ion sieves has gone through, there has been no technical breakthrough in the high dissolution rate of manganese-based lithium ion sieves. Professionals are paying more and more attention to the research and development of other types of low-dissolution lithium ion sieves.

[0005] Patent CN108543516B discloses a lithium ion selective adsorbent, a preparation method and a process for extracting lithium from brine. A nickel-doped modified manganese-based lithium ion sieve is loaded on a carbon nitride carrier with photocatalytic degradation performance. Carbon nitride is used to photocatalytically degrade organic pollutants in the brine, thereby slowing down the decrease in lithium ion adsorption capacity and cycle life of the lithium ion sieve during the cyclic adsorption process. However, the preparation process of the carbon nitride photocatalyst is complicated and the preparation cost is too high.

[0006] The applicant disclosed a solar-catalyzed self-cleaning aluminum salt lithium ion sieve filler and its preparation method in patent application CN116870854A, which loaded microcrystalline aluminum hydroxide onto a magnetic activated carbon carrier and pressed it into a filler, which is intended to be used for adsorption and extraction of lithium from oil and gas field brine. The active ingredient of the filler is xLiCl·2Al(OH)3·4H2O·yBiOCl, where x=0.05-1, y=0.01-0.1, and n=2,3,4. However, the lithium ion exchange capacity of aluminum hydroxide-based lithium ion sieves is small, the adsorption and desorption rate is very slow, and the amount of water consumed by the regeneration of the ion sieve filler is too large.

[0007] Patent 115974099A discloses a three-dimensional titanium phosphate framework top oxygen-shared lithium ion sieve and its preparation method. The lithium ion sieve is a delithiation product of a modified lithium titanium phosphate precursor doped with chromium ions and zirconium ions. The molecular formula of the modified lithium titanium phosphate is Li1+xTi y Cr x Zr 2-x-y (PO4)3, wherein x = 0.1-1.4, y = 0.4-0.6. This type of ion sieve also has the problems of low adsorption capacity and poor anti-pollution ability.

[0008] Patent 117208930A discloses a green preparation method of a Cu-doped mesoporous aluminum phosphate type lithium ion adsorbent and its application, comprising mechanically mixing a phosphorus source, an aluminum source and a template agent in a certain molar ratio; then transferring the mixture to a polytetrafluoroethylene-lined reactor for solidification; washing, drying and calcining the solidified product to obtain mesoporous aluminum phosphate; the mesoporous aluminum phosphate-based lithium ion sieve prepared by the present invention is synthesized by a solvent-free method, and has the characteristics of simple and easy steps, high atomic utilization rate and no pollution; however, the technical problems of low lithium ion saturation adsorption capacity and poor anti-pollution ability of the lithium ion sieve are not solved.

[0009] Japanese ion exchange material expert Kenta Ooi summarized various inorganic ion exchange materials in his monograph "Inorganic Ion Exchange Materials", and disclosed in the book that protonated spodumene LiAlSi2O6 is a potential lithium ion exchange material. Natural spodumene is an α-type spodumene crystal structure. Although its theoretical lithium content is as high as 3.75%, it is not suitable to be directly used as a lithium ion sieve precursor because the lithium atoms are covalently bonded to aluminum oxides very firmly, the specific surface area of ​​the ore material is small, and the reaction activity is low.

[0010] Patent 116786078B discloses a lithium iron silicate modified spodumene slag lithium ion sieve, its precursor and preparation method, wherein the spodumene slag is acidified and roasted to obtain a primary roasted material, and then the modified spodumene slag is doped with newly prepared lithium iron silicate, and the lithium ion sieve is obtained after roasting again. This process has the environmental advantages of low raw material price and full utilization of waste, but the process of acidification and secondary roasting of spodumene slag is complicated and polluted seriously, and the lithium ion saturation adsorption capacity of the obtained lithium ion sieve is relatively low, and the anti-pollution ability is poor. The photocatalytic self-cleaning lithium ion sieve has the advantages of anti-pollution and recyclability, and is the key direction of future research and development of lithium ion sieve. Doping photocatalytic materials in lithium ion sieve materials is a convenient way to prepare photocatalytic self-cleaning lithium ion sieves. Summary of the invention

[0011] The invention aims to provide a photocatalytic self-cleaning silicate lithium ion sieve, which has a core-shell structure with natural spodumene as a core and bismuth-terbium co-doped spodumene as an outer shell. During preparation, a mixed hydrosol of various components of bismuth-terbium co-doped spodumene is coated on the surface of a natural spodumene carrier, and the pH of the mixed hydrosol is adjusted to 4-6 to form a gel of the mixture; the gel of the mixture is further pressed into shape, dried, subjected to high-temperature transformation treatment and acidified for lithium removal to form a photocatalytic self-cleaning silicate lithium ion sieve; the chemical composition is HAl 1-x-y Bi x Tb y Si2O6 / nH 1-z Li z AlSi2O6, wherein x=0.02-0.2, y=0.01-0.1, z=0.50-0.90, n=1-3; selectively adsorbs lithium ions in simulated oilfield water, and its lithium ion saturation adsorption capacity is 18-27 mg / g. After 5 adsorption and desorption cycles, the lithium ion saturation adsorption capacity only decreases by 3%-5%; it is used for selective adsorption and extraction of lithium from salt lake brine, seawater, oil and gas field water and industrial wastewater.

[0012] The covalent bond between the lithium atom and the silicon-aluminum oxide in the natural spodumene LiAlSi2O6 molecule is very strong, and it is difficult to remove lithium by dilute acid impregnation. Even after acidification and roasting, the lithium ion desorption rate is very slow. The lithium ion saturation adsorption capacity of protonated spodumene is usually less than 10 mg / g, which is not suitable for direct use as a lithium ion sieve. Since protonated spodumene has a lithium ion selective adsorption function, the natural spodumene LiAlSi2O6 is selected as the carrier of the photocatalytic self-cleaning silicate lithium ion sieve in the present invention.

[0013] The spodumene synthesized by the sol-gel method has a low density, a large specific surface area and high activity. It has a fast lithium removal rate in dilute acid aqueous solution and a high lithium ion saturation adsorption capacity. It is an ideal lithium ion sieve precursor. In the process of synthesizing spodumene LiAlSi2O6 by the sol-gel method, bismuth and terbium atoms are co-doped to partially replace the Al atoms in the spodumene LiAlSi2O6 molecules to form a chemical composition of LiAl 1-x-y Bi x Tb y Bismuth and terbium co-doping of Si2O6 spodumene. Bismuth and terbium doping with larger atomic radius only cause lattice distortion of spodumene, and do not change the molecular structure of spodumene; the difference between bismuth and terbium atoms and aluminum atoms is that Bi atoms and compounds can absorb visible light, and terbium atoms and compounds can absorb ultraviolet light and convert it into visible light. They all have good photocatalytic properties. Bismuth and terbium co-doping endow spodumene with visible light catalytic self-cleaning function. In addition, bismuth and terbium atoms with larger atomic radius co-doping replace part of aluminum atoms, widen the migration channel of lithium atoms in the material, weaken the covalent binding force between lithium atoms and silicon aluminum oxide, accelerate the adsorption and desorption rate of lithium ions in aqueous solution, and increase the saturated adsorption capacity.

[0014] In the present invention, a mixed aqueous sol of bismuth and terbium co-doped spodumene components is coated on a natural spodumene carrier, and bismuth and terbium photocatalytic materials are mainly doped in the shell layer irradiated by light energy, and do not penetrate into the inner core where light cannot be incident and does not need self-cleaning, so that the utilization rate of the photocatalytic material is greatly improved, and the specific surface area, lithium ion adsorption and desorption rate and saturated adsorption capacity of the photocatalytic self-cleaning lithium ion sieve are expanded.

[0015] The lithium ion saturation adsorption capacity of the photocatalytic self-cleaning lithium ion sieve of the present invention is as high as 18-27 mg / g, which is mainly contributed by the shell protonated bismuth and terbium co-doped spodumene; followed by the protonated spodumene carrier of the core. After the natural spodumene carrier is subjected to high-temperature transformation treatment, the protonated spodumene carrier can also partially participate in the selective adsorption of lithium ions, thereby assisting in improving the lithium ion saturation adsorption capacity of the lithium ion sieve.

[0016] The bismuth and terbium atoms doped in the present invention partially replace aluminum atoms and mainly exist in the form of bismuth silicate and terbium silicate, which are insoluble in dilute acid aqueous solution and can efficiently photocatalytically degrade organic pollutants attached to the surface of the photocatalytic self-cleaning ion sieve, thereby improving its resistance to organic pollution and delaying the decline of lithium ion saturation adsorption capacity.

[0017] Thanks to the visible light catalytic self-cleaning ability given to the lithium ion sieve of the present invention by the doping of bismuth and terbium atoms and the widening of the lithium ion migration channel caused by lattice deformation, after 5 cycles of selective adsorption and desorption of lithium ions from oilfield water under light, the lithium ion saturation adsorption capacity of the lithium ion sieve only decreased by 3%-5%.

[0018] Another object of the present invention is to provide a method for preparing a photocatalytic self-cleaning silicate lithium ion sieve, comprising the following steps: preparing a mixed aqueous sol of bismuth-terbium co-doped spodumene components, preparing a gel of bismuth-terbium co-doped spodumene components, pressing and drying the gel of bismuth-terbium co-doped spodumene components loaded, high-temperature transformation of bismuth-terbium co-doped spodumene loaded, and acidification and delithiation of bismuth-terbium co-doped spodumene loaded. The specific steps are as follows:

[0019] S1: Stir and mix the newly prepared SiO2 ethanol hydrosol, Al2O3 ethanol hydrosol, bismuth nitrate aqueous solution, and terbium nitrate aqueous solution to obtain a molar ratio of Si:Al:Bi:Tb=2:1:0.02-0.2:0.01-0.1;

[0020] S2: adding 20-100 mesh natural spodumene powder to the mixed hydrosol of bismuth-terbium co-doped spodumene components, and then adding a stoichiometric lithium hydroxide aqueous solution for neutralization; finally adjusting the pH of the mixed hydrosol to 4-6 with 5 mol / l ammonia water to form a gel of bismuth-terbium co-doped spodumene components supported by natural spodumene, and then pressing the gel into a sheet, granular or cylindrical wet filler;

[0021] S3: drying the pressed natural spodumene-loaded bismuth-terbium co-doped spodumene component gel at 110-150° C. for 1-4 h, and completely evaporating the solvent to form a natural spodumene-loaded bismuth-terbium co-doped spodumene dry filler;

[0022] S4: transferring the obtained natural spodumene-supported bismuth-terbium co-doped spodumene dry filler to an alumina crucible, and subjecting the mixture to a high temperature transformation treatment at 650-750° C. for 0.5-2 h, so that both the natural spodumene carrier and the coated bismuth-terbium co-doped spodumene are transformed into a β-type spodumene crystal form, and at the same time, the ammonium nitrate contained in the material is completely decomposed and volatilized;

[0023] S5: The bismuth-terbium co-doped spodumene supported by natural spodumene is immersed in a 0.1-0.5 mol / l sulfuric acid or hydrochloric acid aqueous solution for 0.5-2 h, and a photocatalytic self-cleaning silicate lithium ion sieve is obtained after acidification, delithiation, washing, separation and drying. The sieve selectively adsorbs lithium ions in simulated oil field water, and its lithium ion saturation adsorption capacity is 18-27 mg / g, and its chemical composition is HAl 1-x- y Bi x Tb y Si2O6 / nH 1-z Li z AlSi2O6, where x=0.02-0.2, y=0.01-0.1, z=0.50-0.90, n=1-3, the lithium ion saturated adsorption capacity only decreases by 3%-5% after 5 adsorption-desorption cycles.

[0024] The newly prepared spodumene by the sol-gel method has a larger specific surface area and higher reaction activity than natural spodumene, making it more suitable as a precursor for lithium ion sieves. Silicon source, aluminum source and lithium source are required in the preparation. Even if the aqueous sols of the three types of raw materials are mixed evenly, they cannot spontaneously react to form spodumene, and generally require hydrothermal, heating and high-temperature treatment.

[0025] The SiO2 ethanol hydrosol in the present invention is prepared according to a conventional method, that is, tetraethyl orthosilicate is selected as a silicon source, an ethanol aqueous solution with a mass concentration of 30%-70% is used as a solvent, and the nano-silicon dioxide ethanol hydrosol is obtained by acid hydrolysis under the catalysis of a small amount of nitric acid, and the SiO2 particle size is 1-5nm.

[0026] The Al2O3 ethanol hydrosol of the present invention is prepared according to a conventional method, that is, aluminum isopropoxide is selected as an aluminum source, 50%-90% ethanol aqueous solution is used as a solvent, and under the catalysis of a small amount of nitric acid, aluminum isopropoxide is acidically hydrolyzed to obtain an acidic nano-alumina hydrosol, wherein the Al2O3 particle size is 10-50nm.

[0027] In the present invention, lithium hydroxide with good water solubility is selected as the lithium source, which not only has high reaction activity but also can partially neutralize the nitric acid catalyst introduced in the preparation of SiO2 ethanol hydrosol and Al2O3 ethanol hydrosol, thereby reducing the consumption of ammonia neutralizer.

[0028] In the present invention, bismuth nitrate and terbium nitrate chemical reagents with good water solubility are selected as the sources of bismuth and terbium photocatalytic materials.

[0029] Silicon source, aluminum source and lithium source are mixed to form a mixed hydrosol of spodumene components. When the pH of the mixed hydrosol is adjusted to 4-6, the silicon, aluminum and components in the mixed hydrosol are combined at the molecular level, and most of them become spodumene gel. The spodumene gel is pressed into sheets, columns, spheres or other convenient fillers through molds.

[0030] The pressed spodumene gel contains a large amount of organic solvents, water and unconverted raw materials. The heat absorbed during the drying process of the filler completely converts the raw materials into spodumene.

[0031] Natural spodumene and bismuth-terbium co-doped spodumene prepared by the sol-gel method usually have an α-type spodumene structure, in which the covalent bond between the lithium atoms and the silicon-aluminum oxide is very strong, and the lithium atoms cannot be exchanged by protons in dilute acid. Only by high-temperature transformation to β-type spodumene, the binding force between the lithium atoms and the silicon-aluminum oxide is weakened, and the lithium atoms in the molecules can be exchanged by protons in dilute acid.

[0032] In the present invention, when the bismuth-terbium co-doped spodumene undergoes high-temperature transformation, the natural spodumene carrier is also transformed into β-type spodumene, so that the lithium atoms in the carrier also become exchangeable lithium ions, thereby assisting in improving the saturated adsorption capacity of the lithium ion sieve. In order to prevent the bismuth-terbium co-doped spodumene from sintering and reducing the activity and specific surface area, the high-temperature transformation temperature is optimized to be 650-750°C in the present invention.

[0033] During the high-temperature transformation process, the ammonium nitrate salts entrained in the filler are completely volatilized and decomposed, which also promotes the complete co-doping reaction of bismuth and terbium atoms.

[0034] The lithium atoms in the β-type bismuth-terbium co-doped spodumene obtained by high-temperature transformation can be exchanged for lithium by impregnation with inorganic acid and organic acid to form protonated bismuth-terbium co-doped spodumene, which can selectively adsorb lithium ions in a lithium-containing aqueous solution and be converted into bismuth-terbium co-doped spodumene again. In the present invention, low-concentration sulfuric acid or hydrochloric acid is selected to impregnate and exchange lithium, which has the characteristics of fast exchange speed. Since some lithium atoms in the spodumene carrier can also be exchanged, the lithium ion saturation adsorption capacity of the photocatalytic self-cleaning lithium ion sieve is greatly improved.

[0035] The applicant combines photocatalytic technology with lithium ion sieving technology and creatively designs and prepares a photocatalytic self-cleaning lithium silicate ion sieve. Compared with the prior art, the photocatalytic self-cleaning lithium silicate ion sieve has outstanding substantive features and significant technological progress in the following aspects: (1) The photocatalytic self-cleaning lithium silicate ion sieve has a photocatalytic self-cleaning function, strong anti-pollution ability, and stable lithium ion saturation adsorption capacity; (2) The natural spodumene with low cost and lithium ion sieving function is selected as the core, and the active spodumene synthesized by bismuth and terbium co-doping is used as the shell, which has a fast lithium ion adsorption and desorption rate and a high saturation adsorption capacity; (3) The bismuth and terbium photocatalytic material co-doping is used as the shell, and the lithium ion adsorption and desorption rate is fast and the saturation adsorption capacity is high. The doping is mainly carried out on the surface of the shell layer, with high raw material utilization and photocatalytic self-cleaning efficiency; (4) The co-doping of bismuth and terbium atoms with relatively large atomic radius replaces part of the aluminum atoms, which widens the migration channel of lithium atoms in the material molecules, weakens the binding force with silicon aluminum oxide, and increases the lithium ion adsorption and desorption rate and saturated adsorption capacity; (5) The high-temperature transformation treatment is used to improve the lithium ion adsorption and desorption rate and saturated adsorption capacity of bismuth and terbium co-doped spodumene and natural spodumene; (6) The bismuth and terbium co-doping thermochemical reaction and the high-temperature transformation treatment of spodumene are completed in one step, and the sol-gel preparation process is energy-saving and environmentally friendly.

[0036] The beneficial effects of the present invention are embodied in:

[0037] (1) The bismuth-terbium co-doping in the present invention not only gives spodumene a photocatalytic self-cleaning function and anti-pollution ability, but also improves the lithium ion saturation adsorption capacity of the photocatalytic self-cleaning lithium ion sieve;

[0038] (2) In the present invention, the bismuth-terbium co-doping thermochemical reaction and the high-temperature transformation treatment of spodumene are completed in one step, and the sol-gel preparation process is energy-saving and environmentally friendly.

[0039] The raw materials used in the present invention, such as tetraethyl orthosilicate, aluminum isopropoxide, lithium hydroxide, bismuth nitrate, terbium nitrate, ethanol, isopropanol, nitric acid, sulfuric acid, hydrochloric acid, ammonia water and natural spodumene, are all commercially available chemical reagents. The simulated oilfield brine is an aqueous solution of n-octane, sodium dodecylbenzene sulfonate and lithium chloride, with a COD of 100-500 mg / L and a lithium ion concentration of 10-50 mg / L. DETAILED DESCRIPTION

[0040] Example 1

[0041] 122 g (0.2 mol) of newly prepared 10% SiO2 ethanol hydrosol, 102 g (0.05 mol) of 5% Al2O3 ethanol hydrosol, 40 g (0.02 mol) of 20% bismuth nitrate aqueous solution, and 17.3 g (0.01 mol) of 20% terbium nitrate aqueous solution were mixed uniformly; 18.6 g (0.1 mol) of 20-mesh natural spodumene powder was added thereto, and then 50 ml (0.1 mol) of 2 mol / l lithium hydroxide aqueous solution was added for neutralization; finally, the pH of the mixture hydrosol was adjusted to 4-6 with 5 mol / L ammonia water to form a gel of bismuth and terbium co-doped with each component of spodumene supported by natural spodumene, and then the gel was pressed into a cylindrical wet filler. The wet filler was placed in an oven at 110°C and dried for 4 hours, and the solvent was completely evaporated to form a natural spodumene-loaded bismuth-terbium co-doped spodumene dry filler; it was transferred to an alumina crucible and subjected to a high-temperature transformation treatment at 750°C for 2 hours to transform the natural spodumene carrier into a β-type spodumene crystal form, and at the same time, the mixed ammonium nitrate was decomposed and volatilized completely; the natural spodumene-loaded bismuth-terbium co-doped spodumene was immersed in a 0.1 mol / l sulfuric acid aqueous solution for 2 hours, and 39.0 g of a photocatalytic self-cleaning silicate lithium ion sieve was obtained after acidification, delithiation, separation, washing and drying, and its chemical composition is HAl 0.79 Bi 0.2 Tb 0.1 Si2O6 / H 0.5 Li 0.5 AlSi2O6, using LiCl aqueous solution with COD 200mg / L and lithium ion concentration of 20mg / L as simulated oilfield brine for adsorption and lithium extraction experiments, under sunlight and 10-30℃, the adsorption and lithium extraction was carried out for 6-8h, and its lithium ion saturated adsorption capacity was 27mg / g. After 5 adsorption and desorption cycles, the lithium ion saturated adsorption capacity was 26mg / g, and the saturated adsorption capacity only decreased by about 3%.

[0042] Example 2

[0043] 122 g (0.2 mol) of newly prepared 10% SiO2 ethanol hydrosol, 102 g (0.05 mol) of 5% Al2O3 ethanol hydrosol, 4 g (0.002 mol) of 20% bismuth nitrate aqueous solution, and 1.73 g (0.001 mol) of 20% terbium nitrate aqueous solution were uniformly mixed; 56 g (0.3 mol) of 100 mesh natural spodumene powder was added thereto, and then 50 ml (0.1 mol) of 2 mol / l lithium hydroxide aqueous solution was added for neutralization; finally, the pH of the mixture hydrosol was adjusted to 4-6 with 5 mol / L ammonia water to form a gel of bismuth and terbium co-doped with each component of spodumene supported by natural spodumene, and then the gel was pressed into a cylindrical wet filler. The wet filler was placed in an oven at 150°C and dried for 1 hour, and the solvent was completely evaporated to form a natural spodumene-loaded bismuth-terbium co-doped spodumene dry filler; it was transferred to an alumina crucible and subjected to a high-temperature transformation treatment at 650°C for 1 hour to transform the natural spodumene carrier into a β-type spodumene crystal form, and at the same time, the mixed ammonium nitrate was decomposed and volatilized completely; the natural spodumene-loaded bismuth-terbium co-doped spodumene was immersed in a 0.5 mol / l sulfuric acid aqueous solution for 1 hour, and after acidification, delithiation, separation, washing and drying, 74.3 g of a photocatalytic self-cleaning silicate lithium ion sieve was obtained, and its chemical composition is HAl 0.97 Bi 0.02 Tb 0.01 Si2O6 / H 0.9 Li 0.1 AlSi2O6; a LiCl aqueous solution with a COD of 200 mg / L and a lithium ion concentration of 20 mg / L was used as a simulated oilfield brine for adsorption and lithium extraction experiments. The adsorption and lithium extraction was carried out for 6-8 hours under sunlight and 10-30°C. The saturated adsorption capacity of lithium ions was 18 mg / g. After 5 adsorption and desorption cycles, the saturated adsorption capacity of lithium ions was 17.1 mg / g, and the saturated adsorption capacity only decreased by 5%.

[0044] Comparative Example 1

[0045] The silicate lithium ion sieve was prepared according to the method disclosed in patent CN 116786078 B. A LiCl aqueous solution with a COD of 200 mg / L and a lithium ion concentration of 20 mg / L was used as a simulated oilfield brine for adsorption and lithium extraction experiments. The adsorption and lithium extraction were carried out for 6-8 hours under sunlight and at 10-30°C. The saturated adsorption capacity of lithium ions was 6.8 mg / g. After 5 adsorption and desorption cycles, the saturated adsorption capacity of lithium ions was 4.6 mg / g, and the saturated adsorption capacity decreased by 32%.

[0046] Comparative Example 2

[0047] Referring to the method disclosed in patent CN116870854A, a photocatalytic self-cleaning lithium ion sieve was prepared. A LiCl aqueous solution with a COD of 200 mg / L and a lithium ion concentration of 20 mg / L was used as a simulated oilfield brine for an adsorption and lithium extraction experiment. Under sunlight irradiation and 10-30°C, the adsorption and lithium extraction were carried out for 6-8 hours. The saturated adsorption capacity of lithium ions was 3.6 mg / g. After 5 adsorption and desorption cycles, the lithium ion adsorption capacity was 3.2 mg / g, and the saturated adsorption capacity decreased by 11%.

Claims

1. A photocatalytic self-cleaning silicate lithium ion sieve, characterized in that: The core-shell structure is formed by taking natural spodumene as the core and bismuth-terbium co-doped spodumene as the shell. During the preparation, a mixed hydrosol of each component of bismuth-terbium co-doped spodumene is coated on the surface of the natural spodumene carrier, and the pH of the mixed hydrosol is adjusted to 4-6 to form a gel of the mixture; the gel of the mixture is further pressed into shape, dried, subjected to high-temperature transformation treatment and acid-delithiation to form a photocatalytic self-cleaning silicate lithium ion sieve, the chemical composition of which is HAl 1-x-y Bi x Tb y Si2O6 / nH 1-z Li z AlSi2O6, wherein x=0.02-0.2, y=0.01-0.1, z=0.50-0.90, n=1-3; selectively adsorbs lithium ions in simulated oilfield water, and its lithium ion saturation adsorption capacity is 18-27 mg / g. After 5 adsorption and desorption cycles, the lithium ion saturation adsorption capacity only decreases by 3%-5%; can be used for selective adsorption and extraction of lithium from salt lake brine, seawater, oil and gas field water and industrial wastewater.

2. A method for preparing a photocatalytic self-cleaning silicate lithium ion sieve, characterized in that The method comprises five parts: preparation of mixed aqueous sol of various components of bismuth-terbium co-doped spodumene, preparation of gel of various components of bismuth-terbium co-doped spodumene, pressing and drying of gel of various components of bismuth-terbium co-doped spodumene, high-temperature transformation of the loaded bismuth-terbium co-doped spodumene, and acidification and delithiation of the loaded bismuth-terbium co-doped spodumene. The specific operation steps are as follows: S1: Mix the newly prepared SiO2 ethanol hydrosol, Al2O3 ethanol hydrosol, bismuth nitrate aqueous solution and terbium nitrate aqueous solution uniformly, and control the feeding molar ratio of Si:Al:Bi:Tb=2:1:0.02-0.2:0.01-0.1; S2: adding 20-100 mesh natural spodumene powder to the mixed hydrosol of bismuth-terbium co-doped spodumene components, and then adding a stoichiometric lithium hydroxide aqueous solution for neutralization; finally adjusting the pH value of the mixture to 4-6 with 5 mol / l ammonia water to form a gel of bismuth-terbium co-doped spodumene components supported by natural spodumene, and then pressing the gel into a sheet, granular or cylindrical wet filler; S3: drying the pressed natural spodumene-loaded bismuth-terbium co-doped spodumene component gel at 110-150° C. for 1-4 h, and completely evaporating the solvent to form a natural spodumene-loaded bismuth-terbium co-doped spodumene dry filler; S4: transferring the obtained natural spodumene-supported bismuth-terbium co-doped spodumene dry filler to an alumina crucible, and subjecting the mixture to a high temperature transformation treatment at 650-750° C. for 0.5-2 h, so that both the natural spodumene carrier and the coated bismuth-terbium co-doped spodumene are transformed into a β-type spodumene crystal form, and at the same time, the ammonium nitrate contained in the material is completely decomposed and volatilized; S5: The bismuth-terbium co-doped spodumene supported by natural spodumene is immersed in a 0.1-0.5 mol / l sulfuric acid or hydrochloric acid aqueous solution for 0.5-2 h, and a photocatalytic self-cleaning silicate lithium ion sieve is obtained after acidification, delithiation, washing, separation and drying. The sieve selectively adsorbs lithium ions in simulated oil field water, and its lithium ion saturation adsorption capacity is 18-27 mg / g, and its chemical composition is HAl 1-x- y Bi x Tb y Si2O6 / nH 1-z Li z AlSi2O6, wherein x=0.02-0.2, y=0.01-0.1, z=0.50-0.95, n=1-3, the saturated adsorption capacity of lithium ions only decreases by 3%-5% after 5 adsorption-desorption cycles.

Citation Information

Patent Citations

  • A lithium-ion selective adsorbent, its preparation method, and a process for extracting lithium from brine.

    CN108543516B

  • Solar catalytic self-cleaning aluminum salt lithium ion sieve filler and preparation method thereof

    CN116870854A